Winter Wheat Graze-Out - Jones, Rodney; Sartwelle III, James D.; O'Brien, Daniel M. (My University, 1996)
This budget estimates short run costs and returns for both a steer and heifer wheat grazing program.
MF1010_1996-10
Keywords: MF1010; Economics; Livestock; Crops; MF